Phenotypic Characterization of Tomato (Lycopersicon esculentum) Germplasm to Develop the High Yielding Breeding Resource in Bangladesh - Quamruzzaman, A K M; Akter, L.; Islam, F. (Discoveries in Agriculture and Food Sciences, 2023)
A study was conducted with 28 tomato germplasm/variety at the Olericulture Division of Horticulture Research Centre, BARI, during the winter season of 2021-22 to evaluate the yield and yield related components. There was significant variability observed among the 28 tomato germplasm varieties. Significant variation was observed in the number of fruits per plant and single fruit weight, while the range was 15-52 and 23-97g, respectively. In this study, eleven germplasms produced more than 70.00 t/ha, with SLA34 producing the highest yield (95.24 t/ha), followed by SLA15-7 (91.24 t/ha), SLA15-1B (86.63 t/ha), SLA36 (85.47t/ha), BARI Tomato-15 (81.35 t/ha), SLA15-6 (79.43t/ha), SLA15-1 (77.22 t/ha). The range of yield was obtained from 26.57-95.24 t/ha. The range of TSS was 2.9% (SLA20) to 6.5% (SLA34), while higher TSS contained germplasm were viz., SLA34 (6.5%), SLA15-5, SLA15-6 (5.2%), SLA15, SLA32 (5.1%). Significant variation was observed for TYLCV infection and leaf-sucking pest infestation, which varied from 0–10% and 0–20%, respectively. Considering yield and yield contributing parameters, the germplasm viz., SLA34, SLA15-7, SLA15-1B, SLA36, SLA15-6, SLA30, SLA15-1, SLA15-4, SLA27, SLA15, SLA32, and SLA11 may be investigated further for developing better tomato varieties.